Highly Selective and Portable Fluorescence Turn-On Detection of Sc 3+ in Ore and Water Based on Strong Lewis Acid-Base Coordination - Chen, Xueshan; Zhang, Zhankuo; Wu, Yuke; Zhou, Jinyan; Wei, Yingnan; Zhang, Jinyi; Zheng, Chengbin (Analytical chemistry (Washington), 2024)
Detecting scandium (Sc) with high selectivity and sensitivity is a challenging task due to its chemical similarity to other rare earth ions. Our findings show that the fluorescence of the complex fluorescent indicator calcein (CL) is quenched under acidic conditions (pH = 2), and Sc strongly inhibits this process. The results demonstrate that CL forms multimers and precipitates out of the solution under acidic conditions, while Sc causes a significant decrease in the scattering intensity of the solution. Additional experiments revealed that the strong Lewis acid nature of Sc complexes with the carboxyl groups of CL leads to increased dispersion of CL even under acidic conditions, thus enhancing its absorption and fluorescence. The complexation ratio of Sc and CL was investigated through spectral titrations and theoretical calculations. The interaction between Sc and CL is the strongest among rare earth and common metal ions due to the smallest ionic radius, resulting in high selectivity. The fluorescence turn-on strategy had a linear range of 0.04 to 2.25 μM under optimal conditions, with a detection limit of 20 nM for Sc . The combination of 3D printing and a smartphone program allows for portable on-site analysis of Sc . Mineral and water samples were used to demonstrate the potential of this strategy for the rapid, selective, and sensitive analysis of low levels of Sc .